ANALISIS EKSPLANATIF PREVALENSI BUNUH DIRI IMPLIKASI STRES AKADEMIK TERHADAP PENGARUH SOSIAL MAHASISWA DI KOTA MALANG - Mutia Lestari Abidin; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
Stress due to academic problems is often a big challenge, especially for students. Students are in adolescence who have emotional conditions that are not yet mentally stable enough. So teenagers tend to be more irritable, stressed and have difficulty controlling their emotions. The issue of ending life also has a significant impact on the social structure in Malang. This article examines the implications of academic stress on the social influence of students in Malang City from the perspective of suicide epidemiology. Using the literature review method, this study explores the level of academic stress and suicidal tendencies among university students. The research method used is a literature review that focuses on one particular topic of discussion. The literature review also provides an overview of the identification of student suicides in the city of Malang. In addition, this ending of life event is also associated with Emile Durkheim's theory of suicide, which is categorized into four, namely egoistic, altruistic, anomie and fatalistic, to know in which group this case is and to know how the characteristics of the individual who ends his life, before deciding to end his life. Then the purpose of this article is to find out what influences or factors can be the reason why students in Malang City choose to end their lives, then what methods can prevent and reduce cases of ending their lives especially among students.